2010
DOI: 10.1063/1.3333436
|View full text |Cite
|
Sign up to set email alerts
|

Double-diffusive Marangoni convection in a rectangular cavity: Onset of convection

Abstract: Double-diffusive Marangoni convection in a rectangular cavity with horizontal temperature and concentration gradients is considered. Attention is restricted to the case where the opposing thermal and solutal Marangoni effects are of equal magnitude ͑solutal to thermal Marangoni number ratio R =−1͒. In this case a no-flow equilibrium solution exists and can remain stable up to a critical thermal Marangoni number. Linear stability analysis and direct numerical simulation show that this critical value corresponds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Thermocapillary flow for silicone oil 1.5 cSt with the depth of 2 mm follows the Feigenbaum route, which undergoes 2 period-doubling bifurcations. The proportional relationship between oscillatory frequency and Ma obtained in our experimental study is in agreement with numerical results by Yok-Sheung Li et al [21,22].…”
Section: Discussionsupporting
confidence: 82%
“…Thermocapillary flow for silicone oil 1.5 cSt with the depth of 2 mm follows the Feigenbaum route, which undergoes 2 period-doubling bifurcations. The proportional relationship between oscillatory frequency and Ma obtained in our experimental study is in agreement with numerical results by Yok-Sheung Li et al [21,22].…”
Section: Discussionsupporting
confidence: 82%
“…Validations of both the linear stability analysis and direct numerical simulation procedures were detailed in Chen et al, 17 where these two methods were successfully used to investigate the onset of double-diffusive Marangoni convection in a similar configuration.…”
Section: -3mentioning
confidence: 99%
“…However, the nature of the primary bifurcation point had long remained unclear. Very recently, this problem was studied systematically by Chen et al, 17 where it was shown by both linear stability analysis and direct simulation that the first primary instability of the equilibrium corresponds to a supercritical Hopf bifurcation. The flow arising from small disturbance is oscillatory rather than steady.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the numerical implementations of the above procedures can be found in Ferziger and Peric (2002). This numerical code has been successfully used to study a series of double-diffusive convection problems (Chen et al, 2010a(Chen et al, , 2010b(Chen et al, , 2012 …”
Section: Numerical Methods and Validationmentioning
confidence: 99%
“…In order to study such a wide range of geophysical flows, considerable effort has been spent on upgrading the existing hydrostatic model to a nonhydrostatic one, e.g., the hydrostatic ROMS (Regional Oceanic Modeling System) now has a nonhydrostatic version (Kanarska et al, 2007). In the present work, an in-house fully nonlinear, nonhydrostatic numerical code that is originally developed for the study of double-diffusive convection (Chen et al, 2010a(Chen et al, , 2010b(Chen et al, , 2012(Chen et al, and 2013Li et al, 2010;Zhan et al, 2010) is now employed for simulation of ISWs generated by tidal flows over a Gaussian sill. The energy budget of these ISWs is then analyzed.…”
Section: Introductionmentioning
confidence: 99%